KEGAGALAN ISOLASI MINYAK TRAFO - Dedi Nugroho (PSTE UNIMUS, 2010)
Insulation of transformer oil has a role as an insulating material of voltage equipment in electrical equipments, but has other uses such as cooling media or extinguish the arc. Purity insulating oil will determine the strength of the dielectric material. On the condition of purity used oil will be contaminated by other subtances mixed in the oil, the result of oil will become impure and degraded dielectric strength that will ultimately reduce the level of insulation failure, isolation and purification of used oil (no pure oil) was able to significantly increase the insulation failure rate of new oil approach.